A Study Turkish Sports Newspapers’ Coverage of Beşiktaş’s European Matches - Yorgancı, Karl Turgut Maloney (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
The football coverage of Turkish sports newspapers is an area of concern as certain framing decisions raise questions of journalistic ethics in the light of the agenda-setting theory. This study investigates nationalism, militarist metaphors, metaphors of physical fight and the coverage of referees on 116 cover pages of Turkish sports newspapers before and after Beşiktaş played in European competitions during the 2016-2017 and 2017-2018 seasons. The results obtained by using quantitative content analysis show that militarist metaphors and metaphors of physical fight are more common in post-match articles whilst nationalist language is more common in pre-match articles. Nationalist language, militarist metaphors and metaphors of physical fight are most common in post-match articles published after a Beşiktaş victory. There are no positive mentions of the referee and negative mentions occur at the same percentage after a Beşiktaş victory and defeat. Finally, militarist metaphors and metaphors of physical fight are present in more than half of the articles.

ÖZ: Türk spor gazetelerinin futbol yayınları bazı çerçeveleme kararları yüzünden gündem belirleme teorisi ışığında gazetecilik ettiği bakımından endişe yaratmaktadır. Bu araştırmada 2016 - 2017 ve 2017 - 2018 sezonlarındaki Beşiktaş’ın Avrupa kupalarında oynadığı maçlardan bir gün önce ve sonra çıkan Türk spor gazetelerinin kapaklarındaki söylemler incelenmiştir. Seçilen 116 adet gazete kapağında bulunan milliyetçilik, militarist metaforlar, fiziksel kavga metaforları ve hakemle ilgili tutumların irdelendiği çalışmada nicel içerik analizi yöntemi kullanılmıştır. Ulaşılan sonuçlara göre militarist ve fiziksel kavga metaforlarının maçtan sonra çıkan haber metinlerinde daha çok kullanıldığı ve milliyetçi söylemlere ön haberlerde daha sıkca rastlandığını görülmektedir. Maçtan sonra çıkan haberlerde milliyetçiliğin, militarist metaforların ve fiziksel kavga metaforlarının Beşiktaş galibiyetlerinden sonra üst safhada olduğu görülürken, aynı zamanda, hakeme karşı hiç olumlu dil kullanılmadığı ve olumsuz dilin Beşiktaş mağlubiyetleri ve galibiyetleri sonrasında eşit miktarda kullanıldığı sonucuna varılmıştır.
Master of Arts in Communication and Media Studies. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2018. Supervisor: Assoc. Prof. Dr. Metin Ersoy
Keywords: Communication and Media Studies; Turkish Sports journalism--newspapers--Footbal--Beşiktaş; Turkish sports newspapers; Nationalism; Militarist metaphors; Metaphors of physical fight; Referees; Framing; Agenda setting; Journalistic ethics